Influence of ferroelectric dipole on the photocatalytic activity of heterostructured BaTiO3/a-Fe2O3. (2nd April 2019) - Cui, Yongfei; Sun, Huanhuan; Briscoe, Joe; Wilson, Rory; Tarakina, Nadja; Dunn, Steve; Pu, Yongping
Abstract: Using BaTiO3 as a model ferroelectric material we investigated the influence of the ferroelectric dipole on the photocatalytic activity of a heterogeneous BaTiO3 / α -Fe2 O3 photocatalyst. Two distinct BaTiO3 samples were used: BTO and BTO-A. The latter consists more ferroelectric tetragonal phase and thus stronger ferroelectricity. It was found that under identical experimental conditions, the photodecolourisation rate of a target dye using BTO-A/ α -Fe2 O3 under visible light was 1.3 times that of BTO/ α -Fe2 O3 . Photoelectrochemical and photoluminescence analysis confirmed a more effective charge carrier separation in BTO-A/ α -Fe2 O3 . Considering solely the photoexcitation of α -Fe2 O3 in the composite photocatalysts under visible light and the similar microstructures of the two catalysts, we propose that the enhanced decolourisation rate when using BTO-A/ α -Fe2 O3 is due to the improved charge carrier separation and extended charge carrier lifetime arising from an interaction between the ferroelectric dipole and the carriers in α -Fe2 O3 . Our results demonstrate a new process to use a ferroelectric dipole to manipulate the charge carrier transport, overcome recombination, and extend the charge carrier lifetime of the surface material in a heterogeneous catalyst system.